2010
DOI: 10.3109/09638230903531126
|View full text |Cite
|
Sign up to set email alerts
|

Hope and improvements in mental health service providers' recovery attitudes following training

Abstract: Background: Service providers' attitudes towards recovery can improve with formal training. However, it is unclear whether improvements depend on dispositional hope. Aims: To determine whether attitudinal improvements following formal recovery training vary depending on participants' dispositional hope. Method: One hundred and three providers attended formal recovery training and completed measures of recovery knowledge, attitudes, hopefulness and optimism. Results: Training improved providers' recovery knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 16 publications
2
45
3
2
Order By: Relevance
“…Salgado et al (2010) reported professionals with both low and high dispositional hope showed pre‐improvement and postimprovement (low hope z = −2.61, P < 0.01; high hope z = −2.11, P < 0.05) indicating a no interaction between dispositional hope and positive attitude (Salgado et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Salgado et al (2010) reported professionals with both low and high dispositional hope showed pre‐improvement and postimprovement (low hope z = −2.61, P < 0.01; high hope z = −2.11, P < 0.05) indicating a no interaction between dispositional hope and positive attitude (Salgado et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Programmes can be standardised, used across large populations, and allow measurable outputs to be embedded. Studies in the USA [9] and Australia [10] provide some evidence that structured training on critical components of recovery can increase both knowledge and pro-recovery attitudes. A growing number of recovery training programmes, including some that have been granted national accreditation, have been developed in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Ainda assim, permitiu identificar determinantes consonantes com revisões anteriores, salientando a importância dos profissionais de SM na esperança. No entanto, para estes, a esperança não determinou a melhoria das atitudes face às pessoas com doença mental grave, após um programa de formação em recovery (Salgado et al, 2010). Estes achados conduzem à necessidade de repensar as estratégias de formação dos profissionais para a capacitação para a gestão da esperança nos contextos da SM, considerando as formas como comunicam as suas esperanças sobre a recuperação dos clientes e facilitam as esperanças no recovery (Hobbs et al, 2012).…”
Section: Discussionunclassified